Leaders Should be Problem-Solvers Not Problem-Makers: Lesson Learned From Jember, East Java - Koesniar, Airien Marttanti; Maksum, Irfan Ridwan (Indonesian Journal of Multidisciplinary Science, 2023)
In organizations, especially government organizations, there are numerous elements that can impact the effectiveness of a leader, yet the most crucial one is the leader's own qualities and actions. This study aims to provide more specific examples or case studies to illustrate the impact of a leader's policies and actions on governance. Moreover, it would make the argument more compelling and relatable to readers in the context of regional government administration. The methodology used in the research is qualitative methods employed and how the data was collected and analyzed. The methods would establish the research's credibility and provide more context for the findings. Finally, it could be helpful to provide some practical recommendations or suggestions for how organizations or governments can improve their leadership selection and development processes. This study would add value for readers interested in applying the insights from the research to their contexts.